ЭСТЕТИКАЛЫҚ ТӘРБИЯ – ИНСАННЫҢ РУЎХЫЙ МӘДЕНИЯТЫНЫҢ ҚӘЛИПЛЕСИЎИНИҢ ТИЙКАРЛАРЫ - Уразимова, Т.В. (FAN va JAMIYAT, 2025)
The article is devoted to the issues of aesthetic education as the basis for the formation of the spiritual culture of the individual. In this regard, we pay attention to aesthetics as a theory of aesthetic education, aesthetic pedagogy, as a significant one of the main components influencing the development of a creative spiritual personality in the process of learning the basics of fine art.